Digital dissection of the head of the rock dove (Columba livia) using contrast-enhanced computed tomography - Jones, Marc E. H. (Zoological Lett, 2019)
The rock dove (or common pigeon), Columba livia, is an important model organism in biological studies, including research focusing on head muscle anatomy, feeding kinematics, and cranial kinesis. However, no integrated computer-based biomechanical model of the pigeon head has yet been attempted. As an initial step towards achieving this goal, we present the first three-dimensional digital dissection of the pigeon head based on a contrast-enhanced computed tomographic dataset achieved using iodine potassium iodide as a staining agent. Our datasets enable us to visualize the skeletal and muscular anatomy, brain and cranial nerves, and major sense organs of the pigeon, including very small and fragile features, as well as maintaining the three-dimensional topology of anatomical structures. This work updates and supplements earlier anatomical work on this widely used laboratory organism. We resolve several key points of disagreement arising from previous descriptions of pigeon anatomy, including the precise arrangement of the external adductor muscles and their relationship to the posterior adductor. Examination of the eye muscles highlights differences between avian taxa and shows that pigeon eye muscles are more similar to those of a tinamou than they are to those of a house sparrow. Furthermore, we present our three-dimensional data as publicly accessible files for further research and education purposes. Digital dissection permits exceptional visualisation and will be a valuable resource for further investigations into the head anatomy of other bird species, as well as efforts to reconstruct soft tissues in fossil archosaurs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40851-019-0129-z) contains supplementary material, which is available to authorized users.